Excess mortality during the COVID-19 pandemic: a geospatial and statistical analysis in Mogadishu, Somalia. (December 2021) - Warsame, Abdihamid; Bashiir, Farah; Freemantle, Terri; Williams, Chris; Vazquez, Yolanda; Reeve, Chris; Aweis, Ahmed; Ahmed, Mohamed; Checchi, Francesco; Dalmar, Abdirisak
Highlights: Somalia's COVID-19 excess mortality (Mar–Sep 2020) substantially higher than reported The health system struggled to deal with the increasing severity of the pandemic The population remains vulnerable to renewed COVID-19 waves and new variants Geospatial analysis is a promising tool in fragile or crisis-affected settings Abstract: Background: While the impact of the COVID-19 pandemic has been well documented in high-income countries, less is known about the health effects in Somalia, where health systems are weak and vital registration is underdeveloped. Methods: We used remote sensing and geospatial analysis to quantify burial numbers from January 2017 to September 2020 in Mogadishu. We imputed missing grave counts using surface area data. Simple interpolation and a generalised additive mixed growth model were used to predict actual and counterfactual burial rates by cemetery and across Mogadishu during the most likely period of COVID-19 excess mortality and to compute excess burials. We undertook a qualitative survey of key informants to determine the drivers of COVID-19 excess mortality. Results: Burial rates increased during the pandemic, averaging 1.5-fold and peaking at a 2.2-fold increase on pre-pandemic levels. When scaled to plausible range of baseline crude death rates, the excess death toll between January and September 2020 was 3200–11 800. Compared with Barakaat Cemetery Committee's burial records, our estimates were lower. Conclusions: Our study indicates considerable underestimation of the health effects of COVID-19 in Banadir and an overburdened public health system struggling to deal with the increasing severity of the epidemic in 2020.